Cooperation of Syd-1 with Neurexin synchronizes pre-with postsynaptic assembly - Owald, D; Khorramshahi, O; Gupta, V; Banovic, D; Depner, H; Fouquet, W; Wichmann, C; Mertel, S; Eimer, S; Reynolds, E; Holt, M; Aberle, H; et al. (2012)
Synapse formation and maturation requires bidirectional communication across the synaptic cleft. The trans-synaptic Neurexin-Neuroligin complex can bridge this cleft, and severe synapse assembly deficits are found in Drosophila melanogaster neuroligin (Nlg1, dnlg1) and neurexin (Nrx-1, dnrx) mutants. We show that the presynaptic active zone protein Syd-1 interacts with Nrx-1 to control synapse formation at the Drosophila neuromuscular junction. Mutants in Syd-1 (RhoGAP100F, dsyd-1), Nrx-1 and Nlg1 shared active zone cytomatrix defects, which were nonadditive. Syd-1 and Nrx-1 formed a complex in vivo, and Syd-1 was important for synaptic clustering and immobilization of Nrx-1. Consequently, postsynaptic clustering of Nlg1 was affected in Syd-1 mutants, and in vivo glutamate receptor incorporation was changed in Syd-1, Nrx-1 and Nlg1 mutants. Stabilization of nascent Syd-1-Liprin-α (DLiprin-α) clusters, important to initialize active zone formation, was Nlg1 dependent. Thus, cooperation between Syd-1 and Nrx-1g-Nlg1 seems to orchestrate early assembly processes between pre-and postsynaptic membranes, promoting avidity of newly forming synaptic scaffolds. © 2012 Nature America, Inc. All rights reserved.